Long-term proton pump inhibitors use and its association with premalignant gastric lesions: a systematic review and meta-analysis - Zheng, Zeyi; Lu, Ziyu; Song, Yani (Frontiers in Pharmacology, 2023)
Background: Long-term maintenance therapy with proton pump inhibitors (PPIs) is a common treatment strategy for acid-related gastrointestinal diseases. However, concerns have been raised about the potential increased risk of gastric cancer and related precancerous lesions with long-term PPI use. This systematic review and meta-analysis aimed to evaluate this potential risk.Methods: We searched PubMed, Embase, and the Cochrane Central Register of Controlled Trials for randomised controlled trials published before March 1st, 2023, with no language restrictions. The primary endpoint was the occurrence and progression of gastric mucosal atrophy, intestinal metaplasia, Enterochromaffin-like (ECL) cell hyperplasia, gastric polyps, and gastric cancer during the trial and follow-up. Data were analysed using a random effects model.Results: Of the 4868 identified studies, 10 met the inclusion criteria and were included in our analysis, comprising 27283 participants. Compared with other treatments, PPI maintenance therapy for more than six months was associated with an increased risk of ECL cell hyperplasia (OR 3.01; 95% CI 1.29 to 7.04; P=0.01). However, no significant increase was found in the risk of gastric mucosal atrophy (OR 1.01; 95% CI 0.55 to 1.85; P=0.97), intestinal metaplasia (OR 1.14; 95% CI 0.49 to 2.68; P=0.76), gastric polyps (OR 1.13; 95% CI 0.68 to 1.89; P=0.64), or gastric cancer (OR 1.06; 95% CI 0.79 to 1.43; P=0.71).Conclusions: This systematic review and meta-analysis does not support an increased risk of gastric cancer or related precancerous lesions with long-term PPI maintenance therapy. However, long-term PPI use should be monitored for potential complications such as ECL cell hyperplasia. Further studies are needed to confirm these findings and evaluate the safety of PPI maintenance therapy for acid-related gastrointestinal diseases.